Competence of Judge-Instructor in processus brevior - KRAJCZYŃSKI, KRAJCZYŃSKI (Prawo Kanoniczne, 2019)
Competence of Judge-Instructor in processus brevior Summary The author of the article clarifies briefly some specific obligations and rights of the Instructor, and recalls legal rules the Instructor needs to abide by during Abbreviated Judicial Process.